Website-Based Online Registration System (HEALTH CARE: JURNAL KESEHATAN, 2025)
Information technology is developing rapidly and has a significant impact on various fields, one of which is the health sector, for example, the use of websites in the healthcare system. The purpose of this study is to design a website-based online registration system at the dr.Dini Zulanda clinic. The research method in website development uses the software development life cycle (SDLC) with a waterfall method approach. The programming language used is Hypertext Preprocessor (PHP), and the framework used is Laravel with MySQL as the database. The results of the study created a prototype and online registration website for the dr.Dini Zulanda clinic, but this website still does not have an online consultation service or payment system via the website. So, to overcome this, the website provides a feature to add customer contacts for further consultation services. It is hoped that this system can help provide more efficient services at the dr.Dini Zulanda clinic.